Tubuloside A Induces DNA Damage and Apoptosis in Human Ovarian Cancer A2780 Cells - Türeyen, Ali; Zemheri Navruz, Fahriye; Günay, Sevilay; Erden, Yavuz; Ince, Sinan (European Journal of Therapeutics, 2023)
Objective: Ovarian carcinoma is one of the most lethal gynecological cancers, as it responds later to diagnostic methods and therapeutic responses in advanced stages. Many phytochemical compounds have been shown to be protective against cancer. Tubuloside A (TbA) is the main compound extracted from the plant Cistanche tubulosa, and its pharmacological effects have been studied broadly. Until now, the role of TbA in human ovarian carcinoma is unknown. The goal of this study was to evaluate the effects of TbA on DNA damage and apoptosis in A2780 cell lines. Methods: Different concentrations of TbA (1, 5, 25, 50, and 100 µM) and 5- Fluorouracil (1, 5, 25, 50, and 100 µM) treated to the human ovarian cancer cell (A2780) line for 24 h. After incubation, cell viability (MTT), genotoxicity (Comet analyses), and mRNA expression analyses of apoptotic markers (Caspase-3, Bax, Bcl-2, and p53) were determined. Results: Applied doses of 50 and 100 µM of TbA and 5- Fluorouracil significantly reduced cell viability. Also, TbA increased DNA damage in A2780 cells. Additionally, TbA up-regulated the mRNA expressions of caspase-3, Bax, and p53, which are apoptosis-inducing factors, and down-regulated the expression of Bcl-2. Conclusion: These results show that the p53 and caspase-3 signaling pathways may exhibit a key role in TbA-associated effects on A2780 cells and TbA may be a potential drug aspirant for ovarian cancer therapy.